Undergraduate and postgraduate education of the Republic of Kazakhstan: past and present. (Journal of Educational Sciences, 2016)
The article highlights the main trends of development of the system of higher and postgraduate education of the Republic of Kazakhstan from the beginning of the 90s to the present. Since independence Kazakhstan conducted a series of reforms in education, including in the field of higher and postgraduate education. This included implementation of the basic principles of the Bologna Process: a three-tiered model of training, independent evaluation of the quality through the process of accreditation of higher education institutions and educational programs, credit system and the autonomy and the Diploma Supplement. Moreover, the access to higher education was expanded through unified national test and increase of educational public order for higher education programs. However, in order to further develop the system of higher and postgraduate education follow-up work is needed to improve the scientific potential of universities, the participation of stakeholders in defining the content of higher and postgraduate education, and government support for the quality assurance system.
Keywords: undergraduate and postgraduate education; quality assurance; accreditation